Changes in the Religious Behavior of Santri through Tabligh Communication at Qotrun Nada Islamic Boarding School, Depok - Akbar Zakiy Hidayatulah; Nasichah N; Syarfa Kamila Ali; Shafira Azzahra Sudrajat (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Technological advancement and contemporary lifestyle changes have influenced the way young people practice religious life, particularly within the pesantren (Islamic boarding school) environment. This study aims to examine the role of tabligh communication in shaping and transforming the religious attitudes of santri (students). The research employs a qualitative method, collecting data through interviews, observations, and document analysis, which are then analyzed descriptively. The findings indicate that tabligh communication employing dialogical approaches, exemplary conduct by ustadz, and routine worship practices successfully enhances religious understanding and fosters strong Islamic character. In conclusion, tabligh communication significantly contributes to strengthening spiritual commitment and developing sustainable religious behavior in pesantren, thereby helping to preserve the faith of the younger Muslim generation.